Modeling of quantum cascade lasers - Shen, Xi Wei (Nanyang Technological University, 2024)
Quantum Cascade Lasers represent a novel category of semiconductor lasers, distinctively crafted from multiple quantum wells/barriers to facilitate emission in the mid-infrared to Terahertz spectrum, spanning wavelengths approximately between 3 to 300 µm. The unique aspect of QCLs lies in their emission wavelength not being confined by the material’s bandgap but rather being adjustable through the precise engineering of the quantum wells/barriers’ thicknesses. This attribute has catapulted QCLs to the forefront of technology, enabling them to produce emissions at virtually any desired wavelength within the mid-infrared and Terahertz ranges. As a result, QCLs have found extensive utility in a diverse array of fields including, but not limited to, sensing, spectroscopy, imaging, atmospheric monitoring, security, defense, astronomy, and notably, free-space communications. This thesis endeavors to contribute to the advancement of QCL technology by introducing a high-performance, long-wavelength QCL, which has potential to be tailored for enhancing free-space communication systems.